Hospital survival upon discharge of ill-neonates transported by ground or air ambulance to a tertiary center - Jorge Luis Alvarado-Socarras; Alvaro Javier Idrovo; Anderson Bermon (Elsevier, 2016)
Abstract Objective: To evaluate the differences in hospital survival between modes of transport to a tertiary center in Colombia for critically ill neonates. Methods: Observational study of seriously ill neonates transported via air or ground, who required medical care at a center providing highly complex services. Data on sociodemographic, clinical, the Transport Risk Index of Physiologic Stability (TRIPS), and mode of transport were collected. Patients were described, followed by a bivariate analysis with condition (live or dead) at time of discharge as the dependent variable. A multiple Poisson regression with robust variance model was used to adjust associations. Results: A total of 176 neonates were transported by ambulance (10.22% by air) over six months. The transport distances were longer by air (median: 237.5 km) than by ground (median: 11.3 km). Mortality was higher among neonates transported by air (33.33%) than by ground (7.79%). No differences in survival were found between the two groups when adjusted by the multiple model. An interaction between mode of transport and distance was observed. Live hospital discharge was found to be associated with clinical severity upon admittance, birth weight, hemorrhaging during the third trimester, and serum potassium levels when admitted. Conclusions: Mode of transport was not associated with the outcome. In Colombia, access to medical services through air transport is a good option for neonates in critical condition. Further studies would determine the optimum distance (time of transportation) to obtain good clinical outcomes according type of ambulance.